2020
DOI: 10.3390/foods9050628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera L. Leaf Powder Addition on the Phenolic Bioaccessibility and on In Vitro Starch Digestibility of Durum Wheat Fresh Pasta

Abstract: Fresh pasta was formulated by replacing wheat semolina with 0, 5, 10, and 15 g/100 g (w/w) of Moringa oleifera L. leaf powder (MOLP). The samples (i.e., M0, M5, M10, and M15 as a function of the substitution level) were cooked by boiling. The changes in the phenolic bioaccessibility and the in vitro starch digestibility were considered. On the cooked-to-optimum samples, by means of ultra-high-performance liquid chromatography-quadrupole time-of-flight (UHPLC-QTOF) mass spectrometry, 152 polyphenols were putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…69.3; p < 0.05). Similarly, Rocchetti et al [8] reported a gradual decrease in the in vitro starch HI of cooked to optimum semolina fresh pasta as the amount of MOLP in the recipe increase. The decrease in the HI values as a function of the substitution level of MOLP could be related to the chemical composition of the samples, as well as to the different behaviour of the starch system during the heating of processing, as outlined in the pasting properties of the starch within each specific biscuit formulation (Fig.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…69.3; p < 0.05). Similarly, Rocchetti et al [8] reported a gradual decrease in the in vitro starch HI of cooked to optimum semolina fresh pasta as the amount of MOLP in the recipe increase. The decrease in the HI values as a function of the substitution level of MOLP could be related to the chemical composition of the samples, as well as to the different behaviour of the starch system during the heating of processing, as outlined in the pasting properties of the starch within each specific biscuit formulation (Fig.…”
mentioning
confidence: 85%
“…Previous experiments conducted on wheat-based cookies and pasta showed that the addition of MOLP in the range of 10-15% can contribute to improve the overall nutritional value [8,10,11]. In addition, Rocchetti et al [8] reported 1 3 that the inclusion of MOLP in semolina fresh pasta contributed to modulate the in vitro starch digestion of optimally cooked samples. Considering the sensory attributes, Dachana et al [10] reported that an addition of beyond 10% level of MOLP produced unacceptable wheat-based biscuits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations